Displacement Analysis for Laminated Beams Under Thermal Stress: A Review - Mr. Durgesh H. Tupe, Mr. Mahesh V. Ghotkar, Renu P Pathak, Satyawan L. Dhondge (Mathematical Statistician and Engineering Applications, 2022)
Background: In this article presents a comprehensive overview of the literature on the analysis of shear deformable isotropic, laminated composite, and sandwich beams under bending based on comparable single layer theories, layerwise theories, zig-zag theories, and exact elasticity solutions. Additionally, a review of the literature on laminated and layerwise beam finite element modelling based on traditional and advanced theories is also done. For the benefit of other researchers working in this subject, the displacement fields of several equivalent single layer and layerwise theories are compiled in the current study.